DESCRIPTION OF THE MODEL OF THE INTERACTION OF WATER AND AIR FLOWS IN THE FLOW ZONE OF THE COOLING TOWER - Matbabayev, M.M.; Inomov , J. (Educational Research in Universal Sciences, 2023)
When calculating the process of heat and mass transfer between water and air, it is necessary to take into account two mechanisms: convective heat transfer from the heated water to the air passing through the cooling flow path and heat transfer due to the mass transfer of evaporated water to the air stream. The cooling process is difficult to describe because the parameters of the supplied (sprayed) water and the incoming air flow vary from section to section at height n during the initial period of the process.